Benefit-sharing from protected area tourism: A 15-year review of the Rwanda tourism revenue sharing programme - Snyman, Susan (Sue); Fitzgerald, Kathleen; Bakteeva, Anastasiya; Ngoga, Telesphore; Mugabukomeye, Benjamin (Frontiers in Sustainable Tourism, 2023)
The success of protected areas depends to a large degree on the support of local communities living in and around these areas. Research has shown that where communities receive tangible and/or intangible benefits, from protected areas they are often more supportive of conservation. Rwanda introduced a tourism revenue sharing policy in 2005 to ensure that local communities receive tangible benefits specifically from protected area tourism and to enhance trust between the Rwanda Development Board (the then Rwanda Office of Tourism and National Parks) and local communities, and to incentivize the conservation of wildlife and protected areas. This study reviewed the tourism revenue sharing programme over the last 15 years, including primary and secondary data, which included interviewing more than 300 community members living around three national parks, as well as other relevant stakeholders. The results show that the tourism revenue sharing programme has resulted in a positive linkage between the national parks and development. Since 2005, ~80% of the funding was used for infrastructure and education projects. The funds are distributed through local community cooperatives, and most local people who are members of these cooperatives had received or were aware of tangible benefits received by the community and tended to have more positive attitudes toward tourism and the national parks. Despite a large amount of tourism revenue being disbursed over the 15-year period, there are still challenges with the programme and the overall impact could be enhanced. Recommendations as to how to address these are presented.